Broad Spectrum Algae Compounds Against Viruses - Reis, Jacqueline Graff; Cadamuro, Rafael Dorighello; Cabral, Ariadne Cristiane; Thaís da Silva, Izabella; Rodríguez-Lázaro, David; Fongaro, Gislaine (Frontiers in Microbiology, 2022)
The pharmaceutical industry is currently trying to develop new bioactive compounds to inactivate both enveloped and non-enveloped viruses for therapeutic purposes. Consequently, microalgal and macroalgal bioactive compounds are being explored by pharmaceutical, as well as biotechnology and food industries. In this review, we show how compounds produced by algae include important candidates for viral control applications. We discuss their mechanisms of action and activity against enveloped and non-enveloped viruses, including those causing infections by enteric, parenteral, and respiratory routes. Indeed, algal products have potential in human and animal medicine.